Human papillomavirus and coinfections with Chlamydia trachomatis, Gardnerella vaginalis, and Trichomonas vaginalis in self-collected samples from female sex workers in the Central-Western region of Brazil - Larissa Z. A. Lugo; Camila M. B. Jacob; Ana Paula Machado; Flávia G. Almeida; Leandro S. Ávila; Thiago T. M. Prata; Cacilda T. J. Padovani; Alda Maria T. Ferreira; Carlos Eurico S. Fernandes; Inês Aparecida Tozetti (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: Human papillomavirus (HPV) is intimately associated with cervical cancer, and the presence of coinfections, such as with Chlamydia trachomatis, Gardnerella vaginalis and Trichomonas vaginalis, may potentiate or facilitate HPV infection. Female sex workers are considered vulnerable to the acquisition of these infections due to exposure to risk factors. Objective: To determine HPV infection, viral types and coinfections in self-collected samples from female sex workers. Methods: Self-collected samples from female sex workers, of vaginal canal and uterine cervix, were subjected to HPV-deoxyribonucleic acid (DNA) detection, viral genotyping by type-specific polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP), and the detection of coinfection. Results: HPV-DNA was detected in 19.4% of the samples, and HPV 31, 6, and 53 were the most frequently detected types. There was a predominance of high-risk oncogenic HPV (HR-HPV) and a strong presence of simultaneous infections with multiple HPV types (84.6%). Coinfections with both HPV and C. trachomatis, and HPV and G. vaginalis were detected. The variables that were statistically associated with HPV infection and the presence of multiple infections were non-use of condoms and non-compliance with regular cervical cytology screening. Conclusion: The results highlight the importance of more comprehensive studies among vulnerable populations, aiming to establish measures to raise awareness about the risks of contracting sexually transmitted infections, as well as to support future studies for introducing HPV vaccines with wider coverage of viral types.